MISINFORMATION AND DISINFORMATION DURING COVID-19: THE EFFECTS AND THE RELEVANT LAWS IN MALAYSIA - Hanis Wahed, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Misinformation and disinformation are increasing as fast as the spreading of Coronavirus disease 2019 or Covid-19. Both happen as a result of the use of social media and technologies. The act of spreading fake news, rumors, and conspiracy theories or giving false information is considered an offence under the laws of Malaysia. However, the number of cases that relate to this offence has been increasing especially during the current pandemic. Thus, this article discusses the effects of the offence and the efforts taken in preventing it from happening. The focus is on the laws that are applicable in the situation. The methodology used is socio-legal research that involves analysing the laws that are applicable in the social situation. The article suggests that further research should be carried out on the applicable laws and amendments should be made to the relevant laws in order to combat the commission of the offence in the future. It is hoped that the suggestion will assist the authority to add more measures in combatting the pandemic and for the public to be more cautious of committing misinformation and disinformation.